Nonpharmacological interventions to promote sleep and rest among hospitalized pediatric patients in general pediatric wards: a best practice implementation project. Issue 1 (14th March 2023) - McGraw, Sarah; Palokas, Michelle; Harbour, Lee
ABSTRACT: Objectives: The aim of this implementation project was to improve compliance with best practice regarding nonpharmacological interventions used to promote sleep and rest in hospitalized pediatric patients in a nonintensive care setting. Introduction: Hospitalized children endure numerous hindrances to sleep and rest, including, but not limited to, noise, pain, anxiety, and interruptions for nursing care. Evidence suggests that a multifaceted approach to sleep promotion can reduce the length of time to sleep onset and the length of nighttime awakenings. It is widely accepted, however, rarely practiced, that proven, low-cost, and noninvasive strategies exist to promote sleep and restoration of hospitalized pediatric patients, which fosters healing and recovery. Methods: This project used the JBI Evidence Implementation framework. A baseline audit of 22 nurses' and 31 patients'/parents'/caregivers' receipt of education on strategies to promote sleep and rest was obtained via survey; baseline data were also obtained from nurses regarding whether or not a multifaceted approach to sleep promotion is utilized and/or if an evidence-based protocol regarding sleep promotion is in place. Targeted strategies, including a protocol and nurse/patient education of multifaceted approaches to sleep, were then implemented, and a follow-up audit of 25 nurses and 32 patients/caregivers was completed. Results: Overall, postimplementation audits revealed 93% compliance with best practice, a 78% increase from baseline audits of 15%. Baseline data revealed poor knowledge of and/or compliance with each of the four audit criteria: nurse education on strategies to promote sleep and rest, the use of an evidence-based protocol regarding sleep promotion, a multifaceted approach to sleep promotion, and patient and/or caregiver education regarding sleep promotion. Postimplementation data, however, showed improvement in each of these areas. Conclusion: Deficiencies in best practice recommendations for the promotion of sleep and rest in pediatric patients admitted to general wards were identified, interventions were implemented, and results were beneficial. Further investigation could be taken to assess the long-term effectiveness of interventions and/or sleep quality of patients while hospitalized. Moreover, postimplementation audits should be administered to parents near the end of their stay, after they have had time to implement optional interventions, if they choose.